Shopping Lifestyle dan Diskon terhadap Impulse Buying di E-Commerce - Putri Agustin Dwi Ningrum; Hery Pudjoprastyono (IPM2KPE, 2023)
This study aims to analyze the effect of shopping lifestyle and discounts on impulse buying in e-commerce Shopee for UPN